From Forest to a Song; A Process of Extracting the Soundscape of Nature into Art Songs - Alia Farahin Abd Wahab; Khairunnisa Diyana Md Noor (PT FORMOSA CENDEKIA GLOBAL, 2022)
The art song is a genre performed mainly by piano and voice. This paper is about the process and the inspirational factor of creating art songs based on the Malaysian urban soundscape. The composer talks about the understanding of the sound and the process of recording certain inspirational sounds, transcribing them, and creating them into a motive. The soundscape chosen by the composer is also a contributing factor to the whole structure and meaning of the song. These motives that have been interpreted based on the recordings are then expanded and made into an art song. There are a few important features that triggered the interest of the composer upon choosing a certain sound as the main inspiration. Besides that, the paper also analyzes how these sounds affected the composer’s understanding of music and its surrounding. In order to write art songs inspired by the urban soundscape in Malaysia, there will be recording sounds of the surroundings and events that the composer feel is appropriate. The composer also includes the interpretation of sound from certain buildings or atmosphere. From these recordings or interpretations, notes are taken out to create a new motive or a short melody from it. The paper includes the process of creating the motives from the recording into a song.